The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fmicb.2016.00489
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Microplate Method (Biolog MT2) for Detection of Fusarium Fungicides Resistance/Sensitivity

Abstract: The need for finding fungicides against Fusarium is a key step in the chemical plant protection and using appropriate chemical agents. Existing, conventional methods of evaluation of Fusarium isolates resistance to fungicides are costly, time-consuming and potentially environmentally harmful due to usage of high amounts of potentially toxic chemicals. Therefore, the development of fast, accurate and effective detection methods for Fusarium resistance to fungicides is urgently required. MT2 microplates (BiologT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…1 ). Although other workers have also reported that microplate method is time saving and efficient (Lapinski et al 1978 ; Frac et al 2016 ), but this is the first report demonstrating the efficiency of 96 well microplate method for siderophore estimation in terms of time, money and being even more efficient than the traditional spectrophotometric method.…”
Section: Resultsmentioning
confidence: 75%
“…1 ). Although other workers have also reported that microplate method is time saving and efficient (Lapinski et al 1978 ; Frac et al 2016 ), but this is the first report demonstrating the efficiency of 96 well microplate method for siderophore estimation in terms of time, money and being even more efficient than the traditional spectrophotometric method.…”
Section: Resultsmentioning
confidence: 75%
“…Tests on plates from the FF MicroPlate ® system by Biolog guarantee obtaining a faithful description of both pure cultures of microorganisms ( Mishra and Nautiyal, 2009 ; Bourdel et al, 2016 ; Frąc et al, 2016 ) and their communities in the soil environment ( Frąc et al, 2014 ; Pająk et al, 2016 ). The functional diversity of fungi isolated from the soil not polluted with DO, determined on FF MicroPlates ® , was higher than that of fungi isolated from the soil polluted with DO, especially at day 270.…”
Section: Discussionmentioning
confidence: 99%
“…To prepare an inoculum, each isolate was cultivated on Potato Dextrose Agar medium (PDA) (Oxoid Ltd., England) with a 3% addition of oak sawdust (SDM), beet pulp (BPM) or, wheat bran (WBM), and control medium (CLM) without any additives, at 27°C in the dark, for 25 days including 7 days with white light exposure for spore formation. 100 μl of the mycelium water suspension was added to wells on the MT2 plate, where previously 50 μl of 1% SD, BP or WB water solution was placed, following the modified procedures of Kadali et al (2012) , Taha et al (2015) and Frąc et al (2016) , in four replicates. The inoculated microplates were incubated at 27°C for 10 days.…”
Section: Methodsmentioning
confidence: 99%